Remote Ultrasonic Imaging of a Wire Arc Additive Manufactured Ti-6AI-4V Component using Laser Induced Phased Array - Lukacs, Peter; Davis, Geo; Stratoudaki, Theodosia; Williams, Stewart; MacLeod, Charles N.; Gachagan, Anthony (2021 IEEE International Instrumentation and Measurement Technology Conference (I2MTC), 2021)
Additive manufacturing (AM) has been revolutionizing the manufacturing industry due to its ability to significantly reduce waste and produce components with intricate shapes. Laser Ultrasonics (LU) is a non-contact and couplant free method to generate and detect ultrasound. LU can accommodate complex component shapes; thus, it has the potential to provide a reliable in-process inspection method for AM components. In recent years the development of Laser Induced Phased Arrays (LIPAs) helped overcome the inherently low signal amplitudes of LU at the non-destructive, thermoelastic regime. In this paper, the Full Matrix Capture data acquisition method is used and a LIPA of 68 elements is synthesized in post processing. The Total Focusing Method imaging algorithm is applied for ultrasonic imaging. The technique is demonstrated on a highly scattering titanium alloy Wire Arc Additive Manufactured (WAAM) component producing high quality ultrasonic images, accurately imaging defects at depths up to 10mm below the inspection surface.